Rigid Nail Fixation in Malunited and Delayed Treated Femoral Fractures in Children Aged 9-12 Years (Journal of Fatima Jinnah Medical University, 2018)
A total of 40 children in the age group 9-12 were selected.they had malunited fractures or fractures which had a shortening of at least 2.5 cm and were treated at least 2 weeks after injury. All these patients were treated with open retrograde k nailing using rigid hand reamers. The fractures united between 2 -6 months. 39 nails were removed between 6-18 months from surgery. There was one infection which settled after nail removal at 3 months.there were no incidences of malunon,non union,refracture, varus, valgus.there was no significant leg length discrepancy(>1.5 cm).,in particular there was no incidence of avn of the femoral head